2008
DOI: 10.1080/00268970701779671
|View full text |Cite
|
Sign up to set email alerts
|

Desorption dynamics of neutral molecules in matrix-assisted laser desorption/ionization

Abstract: This work studies the expansion dynamics of molecules ejected from sample crystals in matrix-assisted laser desorption/ionization (MALDI) reaction. Measurements were made in two steps -sample desorption using a 355 nm pulsed laser beam and gas-phase postionization using a 266 nm laser at various delays. The estimated ion production yield is approximately 10 4 times better than that obtained using conventional MALDI methods. A model system of co-crystallized tryptophan (Trp) analyte and 2,4,6-trihydroxyacetophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
0
11
1
Order By: Relevance
“…Tsai et al demonstrated that in their experiment the velocity distributions of tryptophan and 2,4,6-trihydroxyacetophenone (THAP) cannot be fitted by a single Maxwell-Boltzmann distribution. [39] Instead, they used three Maxwell-Boltzmann distributions to fit the experimental curve. The most probable velocities for these distributions were 61, 154, and 287 m s À1 for tryptophan and 127, 258, and 503 m s À1 for THAP.…”
Section: Desorption Dynamics and Translational Temperaturementioning
confidence: 99%
“…Tsai et al demonstrated that in their experiment the velocity distributions of tryptophan and 2,4,6-trihydroxyacetophenone (THAP) cannot be fitted by a single Maxwell-Boltzmann distribution. [39] Instead, they used three Maxwell-Boltzmann distributions to fit the experimental curve. The most probable velocities for these distributions were 61, 154, and 287 m s À1 for tryptophan and 127, 258, and 503 m s À1 for THAP.…”
Section: Desorption Dynamics and Translational Temperaturementioning
confidence: 99%
“…Keywords: desorption · ionization · laser chemistry · mass spectrometry · photochemistry Studies of neutral molecules are limited by complications in detection. The detection of desorbed neutral molecules in a defined volume above the sample surface by techniques like post-ionization, [17][18][19] gated laser-induced fluorescence (LIF), [20,21] or absorption spectroscopy [21] have been applied for the velocity distribution measurements. Compared to the ion velocity, lower mean velocity values have generally been found for the neutrals.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the velocity distribution obtained from 355 nm desorption of THAP and 266 nm multiphoton ionization at a position 4.5 mm above the surface shows a different shape. [19] A single half-space Maxwellian velocity distribution does not fit the velocity profile.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the optimal s 1 value for heavy ions is inapplicable to light ions because, as reported in the literature, the desorbed materials from the MALDI reaction have roughly equal values for υ [17,22,23]. In such a case, ions that have different masses but are traveling at the same initial velocity result in different E 0 (i.e., higher mass ions exhibit higher E 0 ).…”
Section: Two-ion Conditionmentioning
confidence: 91%